THE PROBLEMS OF DISPUTE SETTLEMENT IN COURT IN IN THE FIELD OF OCCUPATIONAL MEDICINE, RELATED TO THE SPECIFICS OF THESE LEGAL RELATIONS - Гаврылышена, Ксения Валерьевна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Часовских, Елена Владимировна (Medicine in Kuzbass, 2023)
The high prevalence of occupational diseases among workers of the Kemerovo region engaged in production with harmful factors, especially in the coal mining industry, leads to a high number of appeals to Occupational Pathology Centers, and also generates a large number of appeals to judicial authorities in case of refusal due to the disease with the profession. Also in recent years, cases of complaints to judicial authorities on issues of disagreement with the results of the examination of professional suitability have become more frequent. The issues of dispute resolution in connection with obligations arising from harm to the life and health of citizens are within the competence of courts of general jurisdiction. The study aims to consider the problems of dispute settlement in court in the field of occupational medicine related to the specifics of these legal relations. Materials and methods. Regulatory legal acts, national guidelines on occupational pathology, textbooks and articles on the subject of the study. Dialectical method of cognition, general scientific, methods of comparison, analysis and synthesis. Results. In the field of occupational medicine, the vast majority of disputes arise from citizens challenging medical reports issued by medical commissions of Occupational Pathology Centers for the examination of the connection of the disease with the profession. Analyzing the features of the modern judicial method of resolving disputes in the field of occupational pathology, we can come to the conclusion that it seems appropriate to settle the legal framework with the exclusion of conflicting parts, reducing the number of regulatory documents and giving legislative force to the use of such medical documents as clinical recommendations for specific diseases (uniform for the entire territory of the Russian Federation) and the national guidelines on occupational pathology.